Lxr regulates lipid metabolic and visual perception pathways during zebrafish development. (5th January 2016) - Pinto, Caroline Lucia; Kalasekar, Sharanya Maanasi; McCollum, Catherine W.; Riu, Anne; Jonsson, Philip; Lopez, Justin; Swindell, Eric C.; Bouhlatouf, Abdel; Balaguer, Patrick; Bondesson, Maria; Gustafsson, Jan-Åke
Abstract: The Liver X Receptors (LXRs) play important roles in multiple metabolic pathways, including fatty acid, cholesterol, carbohydrate and energy metabolism. To expand the knowledge of the functions of LXR signaling during embryonic development, we performed a whole-genome microarray analysis of Lxr target genes in zebrafish larvae treated with either one of the synthetic LXR ligands T0901317 or GW3965. Assessment of the biological processes enriched by differentially expressed genes revealed a prime role for Lxr in regulating lipid metabolic processes, similarly to the function of LXR in mammals. In addition, exposure to the Lxr ligands induced changes in expression of genes in the neural retina and lens of the zebrafish eye, including the photoreceptor guanylate cyclase activators and lens gamma crystallins, suggesting a potential novel role for Lxr in modulating the transcription of genes associated with visual function in zebrafish. The regulation of expression of metabolic genes was phenotypically reflected in an increased absorption of yolk in the zebrafish larvae, and changes in the expression of genes involved in visual perception were associated with morphological alterations in the retina and lens of the developing zebrafish eye. The regulation of expression of both lipid metabolic and eye specific genes was sustained in 1 month old fish. The transcriptional networks demonstrated several conserved effects of LXR activation between zebrafish and mammals, and also identified potential novel functions of Lxr, supporting zebrafish as a promising model for investigating the role of Lxr during development. Highlights: We performed a microarray analysis of Lxr regulated gene expression in zebrafish. Lxr regulated expression of genes involved in lipid metabolic processes. Lxr ligands induced changes in expression of genes in the neural retina and lens. Lxr activation increased zebrafish embryo yolk absorption. Lxr activation caused morphological alterations in the retina and lens of the zebrafish eye.